Enhancing Energy Generation While Mitigating Noise Emissions in Wind Turbines Through Multi‐Objective Optimization: A Deep Reinforcement Learning Approach - Martín Frutos; Oscar A. Marino; David Huergo; Esteban Ferrer (Wind Energy)
ABSTRACT We develop a torque‐pitch control framework using deep reinforcement learning for wind turbines to optimize the generation of wind turbine energy while minimizing operational noise. We employ a double deep Q‐learning, coupled to a blade element momentum solver, to enable precise control over wind turbine parameters. In addition to the blade element momentum, we use the wind turbine acoustic model of Brooks Pope and Marcolini. Through training with simple winds, the agent learns optimal control policies that allow efficient control for complex turbulent winds. Our experiments demonstrate that reinforcement learning can find optimals at the Pareto front when maximizing energy while minimizing noise. In addition, the adaptability of the reinforcement learning agent to changing turbulent wind conditions underscores its efficacy for real‐world applications. We validate the methodology using a SWT2.3‐93 wind turbine with a rated power of 2.3 MW. We compare the reinforcement learning control with classic controls to show that they are comparable when noise emissions are not taken into account. When including a maximum limit of 45 dBA in the noise produced (100‐m downwind of the turbine), the extracted yearly energy decreases by 22%. The methodology is flexible and allows for easy tuning of the objectives and constraints through the reward definitions, resulting in a flexible multi‐objective optimization framework for wind turbine control. In general, our findings highlight the potential of RL‐based control strategies to improve wind turbine efficiency while mitigating noise pollution, thus advancing sustainable energy generation technologies.